Penerapan Prinsip–Prinsip Hukum untuk Mematuhi Undang–Undang dalam Kasus Pencurian Data Pribadi Pinjaman Online (Pinjol): Ayni Suwarni Herry - Ayni Suwarni Herry (JISOSEPOL: Jurnal Ilmu Sosial Ekonomi dan Politik, 2024)
The existence of the Online Borrowing platform (PINJOL) has made it easier to access sources of funds, but has also had a negative impact on the security of personal data. In this case, the Information and Electronic Transactions Law (UU ITE) is the legal basis that regulates the protection of personal data in Indonesia. This research aims to analyze the application of legal principles in handling cases of personal data theft that occurred on one of the PINJOL platforms, focusing on compliance with the ITE Law regulations. Through the case from the news "Illegal PINJOL Office in Manado Raided Due to Terror in Spreading Customer Data, 'Debtcollector and Owner Become Suspects." Today, we are investigating the legal steps taken by PINJOL, victims and related parties in dealing with incidents of personal data theft. The research results show the importance of the entire PINJOL platform to strengthen data security policies and comply with ITE Law regulations. Protection of user privacy must be a priority and cooperation with law enforcement agencies must be increased to avoid theft of user personal data. Strict legal action also needs to be taken to provide justice for victims of data theft. This case study provides information for the general public to protect personal data as well as for the PINJOL industry to increase user data security and legal awareness in avoiding incidents of personal data theft. This research also emphasizes the importance of maintaining user trust and complying with existing laws in protecting user personal data and privacy in the ever-growing digital era.